A comparative study on the use of interior design in school playscapes with plantscapes versus school playgrounds with synthetic manufactured equipment - Cordero, Christine Maria M.; Mayo, Adelaida V. (Quezon City College of Home Economics, University of the Philippines, 2019)
This research compared two types of school play areas of children with ages 3 to 6 namely, those which make use of plantscapes and natural elements, and those which emphasize synthetic manufactured equipment and play structures. Specifically, the study aimed to determine how the use of plantscapes in the interior design of school playscapes can benefit children. A comparative case study approach was utilized in order to gain a comprehensive analysis of the two types of play areas. The researcher purposively selected four sample schools, two of which had nature-based play areas, while the other two had typical contemporary playgrounds. The study included obnservations of the four play areas with focus on their affordances, and responsive environment, and interviews with the school administration, faculty, and personnel. Through the information collated from interviewees, and based upon the Theory of affordances, and Responsive Environment, the play areas were assessed in terms of their play value. The results of the research show that plantscapes do provide play areas with more affordances than synthetic manufactured equipment and play structures, thus contributing to play value. However, the findings suggest that the presence of plantscapes is not enough. The responsive environment of the play area is also affected by its spatial organization. This spatial organization was found to decrease play value even in play areas with plantscapes. Although advantageous, plantscapes alone cannot give a play area maximum play value; proper configuration of elements through interior design is essential to make this effective. For future researchers who would want to delve into a similar topic, the researcher recommends expanding the research to cover the safety standards and the compliance of play areas with these for the purpose of encompassing this aspect of play value.
Thesis (B.S. Interior Design)--University of the Philippines Diliman
Keywords: Children's playhouses; House plants in interior decoration; Interior decoration -- Philippines; Playgrounds -- Equipment and supplies; Plastic toys